Retrospective Study on Patient Compliance Following Tooth Extraction - Rachel Paul1, Pradeep D2 , Deepa Gurunathan3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aim of this study is to investigate the follow up and compliance of patients who sternly follow thepost operative instructions after non surgical permanent tooth extraction. Data collection were taken frompatients who reported to the college from a particular time period which is from June 2019 to March 2020.The number of extractions and reviewers were obtained from dental archiving software which is offeredby the university. The statistical test that was run was the chi square test using statistical software SPSS byIBM. The results were represented in the form of graphs and pie charts. In this study , the most commonage group were 41-50 years of age(20.38%) and >60 years of age for extractions (25.75%) and reviewsrespectively and the most common gender predilection was found to be male subjects more than femalesubjects (53.55%). The number of patients who returned for reviews were very less (3459 out of 21648)compared to the total number of extractions done. Hence, awareness programs must be initiated and peoplemust be emphasised for vigorous oral hygiene maintenance.